Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline

Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR

Multi-faceted role of melatonin in neuroprotection and amelioration of tau aggregates in alzheimer's disease - Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2018)
Alzheimer's disease (AD) is one of the major age related neurodegenerative diseases whose pathology arises due to the presence of two distinct protein aggregates, viz., amyloid-beta plaques in extracellular matrix and tau neurofibrillary tangles in neurons. Multiple factors play a role in AD pathology, which includes familial mutations, oxidative stress, and post-translational modifications. Melatonin is an endocrine hormone, secreted during darkness, derived from tryptophan, and produced mainly by the pineal gland. It is an amphipathic molecule, which makes it suitable to cross not only blood-brain barrier, but also to enter several other subcellular compartments like mitochondria and endoplasmic reticulum. In this context, the neuroprotective effect of melatonin may be attributed to its role as an antioxidant. Melatonin's pleiotropic function as an antioxidant and neuroprotective agent has been widely studied. However, its direct effect on the aggregation of tau and amyloid-beta needs to be explored. Furthermore, an important aspect of its function is its ability to regulate the process of phosphorylation of tau by affecting the function of kinases and phosphatases. In this review, we are focusing on the pleiotropic function of melatonin on the aspect of its neuroprotective function in tau pathology, which includes antioxidant function, regulation of enzymes, including kinases and enzymes involved in free radical scavenging and mitochondrial protection.
Keywords: Alzheimer's disease; hyperphosphorylation; melatonin; mitochondria; Protein aggregation; tau protein

Actin-mediated microglial chemotaxis via G-protein coupled purinergic receptor in alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease mainly associated with aging, oxidative stress and genetic mutations. There are two pathological proteins involved in AD; Amyloid-beta peptide and microtubule-associated protein Tau (MAPT). The beta- and gamma-secretase enzyme cleaves the Amyloid precursor protein, which results in the formation of extracellular plaques in brain. While, Tau undergoes hyperphosphorylation and other post-translational modifications (PTMs), which eventually generates Tau oligomers, and intracellular neurofibrillary tangles (NFTs) in neurons. Moreover, the brain-resident glia and infiltrated macrophages elevate the level of CNS inflammation, which trigger the oxidative damage of neuronal circuits by reactive oxygen species (ROS) and Nitric oxide (NO). Microglia is the primary immune cell in the CNS, which is continuously surveilling the neuronal synapses and pathogen invasion. Microglia in the resting state is called `Ramified', which possess long surveilling extensions with a small cell body. But, upon activation, microglia retracts the cellular extensions and transform into round migratory cells, called as `Amoeboid' state. Activated microglia undergoes actin remodeling by forming lamellipodia and filopodia, which directs the migratory axis while podosomes formed are involved in extracellular matrix degradation for invasion. Protein-aggregates in malfunctioning synapses and in CNS milieu can be detected by microglia, which results in its activation and migration. Subsequently, the phagocytosis of synapses leads to the inflammatory burst and memory loss. The extracellular nucleotides released from damaged neurons and the cytokine-chemokine gradients allow the neighboring microglia and macrophages to migrate-infiltrate at the site of neuronal-damage. The ionotropic (P2XR) and metabotropic (P2YR) purinergic receptor recognize extracellular ATP/ADP, which propagates through the intracellular calcium signaling, chemotaxis, phagocytosis and inflammation. The P2Y receptors give `find me' or `eat me' signals to microglia to either migrate or phagocytose cellular debris. Further, the actin cytoskeleton helps microglia to mediate directed chemotaxis and neuronal repair during neurodegeneration. Hence, we aim to emphasize the connection between purinergic signaling and actin-driven mechanical movements of microglia for migration and inflammation in AD. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: actin remodeling; Alzheimer's disease; microglia; P2Y signaling; purinergic GPCRs; Tauopathy

Autophagic pathways to clear the tau aggregates in alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin-proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.
Keywords: Alzheimer's disease; Chaperone-mediated autophagy; Lysosome-associated membrane proteins-2A; Macroautophagy; Neurofibrillary tangles; Tau; Tau degradation; Ubiquitin-proteasome system

Cobalt-based metal complexes prevent repeat tau aggregation and nontoxic to neuronal cells - Gorantla, V. Nalini; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease (AD) is a fatal neurodegenerative disorder with an alarming increase in the death rate every year. AD is characterised by an aberrant accumulation of proteins in the form of aggregates. The axonal microtubule-associated protein Tau and arnyloid-beta undergo structural transition to beta-sheet rich structure and form aggregates in neuronal soma as well as in the extracellular region. The loss of Tau from microtubules leads to the disintegration of axon and causing neuronal degeneration. This led to the development of effective drugs against AD, to prevent Tau aggregation. Here, we synthesized and screen metal-based complexes to prevent Tau protein aggregation. ThS fluorescence and TEM suggested the role of synthetic cobalt complexes in inhibiting Tau aggregation. CD spectroscopy showed that these complexes prevented conformational changes in Tau to beta-sheet. CBMCs were not toxic at lower concentrations and formed non-toxic Tau species. L1 and L2 prevented membrane leakage: whereas, higher concentrations of L3 caused membrane leakage as observed by LDH release assay. The overall results indicate the synthetic cobalt complexes to be a promising molecule against AD. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cobalt-based metals; Tau Aggregation; Tau inhibition; Tau toxicity

Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

G-protein coupled receptors and tau-different roles in alzheimer's disease - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Post-translational modification of Tau, a microtubule-associated protein in the neuronal cell, plays a major role in Alzheimer's disease. Tau is an axonal protein expressed in mature neurons that promote the self-assembly of tubulin into microtubules and its stabilization in neurons. Phosphorylation of Tau makes it prone to aggregation at the intra-neuronal region leading to impaired neurotransmission and dementia. Tau aggregates undergo trans-cellular propagation by the release of fibrillar species into the extra-cellular environment from damaged and infected neurons that can be internalized by neighbouring neuronal and glia cells and promotes aggregation in healthy cells. G-protein coupled receptors, the largest group of seven transmembrane receptors, are involved in neuronal signal transduction in response to various signals such as hormones and neurotransmitters. In Alzheimer's disease, GPCRs are involved in phosphorylation of Tau through various downstream kinases such as GSK-3b, CDK-5 and ERKs signalling cascade. Several neuronal GPCRs that are involved in Tau phosphorylation are elaborated in this review. The astrocytic GPCR, Tau phosphorylation mediated by CaS receptors and its propagation by exosomes are also elaborated. In the microglia, the extra-cellular Tau binding to a chemokine GPCR, CX3CR1 triggers its internalization, whereas Tau phosphorylation at specific sites decreases its binding affinity to this receptor. Here we highlight the role of GPCRs in Tau phosphorylation and Tau interaction in different cells of the nervous system. Hence, the role of GPCRs are attaining more attention in the therapeutic field of Alzheimer's disease. Specific agonists/antagonists and allosteric modulators could be the potential target for therapy against GPCR-mediated Tau phosphorylation in Alzheimer's disease. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Alzheimer's disease; GPCRs; microglia; Tau internalization; Tau phosphorylation; Tau propagation

Interaction of Tau with the chemokine receptor, CX3CR1 and its effect on microglial activation, migration and proliferation - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (Cell and Bioscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease that leads to progressive loss of memory and dementia. The pathological hallmarks of AD include extracellular accumulation of amyloid-beta peptides forming senile plaques and intracellular accumulation of Tau oligomers and filamentous species. Tau is a microtubule-binding protein that stabilizes tubulin to form microtubules under physiological condition. In AD/ pathological condition, Tau detaches from microtubules and aggregates to form oligomers of different sizes and filamentous species such as paired helical filaments. Microglia are the resident brain macrophages that are involved in the phagocytosis of microbes, cellular debris, misfolded and aggregated proteins. Chemokine receptor, CX3CR1 is mostly expressed on microglia and is involved in maintaining the microglia in a quiescent state by binding to its ligand, fractalkine (CX3CL1), which is expressed in neurons as both soluble or membrane-bound state. Hence, under physiological conditions, the CX3CR1/CX3CL1 axis plays a significant role in maintaining the central nervous system (CNS) homeostasis. Further, CX3CR1/CX3CL1 signalling is involved in the synthesis of anti-inflammatory cytokines and also has a significant role in cytoskeletal rearrangement, migration, apoptosis and proliferation. In AD brain, the expression level of fractalkine is reduced, and hence Tau competes to interact with its receptor, CX3CR1. In microglia, phagocytosis and internalization of extracellular Tau species occurs in the presence of a chemokine receptor, CX3CR1 which binds directly to Tau and promotes its internalization. In this review, the pathophysiological roles of CX3CR1/fractalkine signalling in microglia and neurons at different stages of Alzheimer's disease and the possible role of CX3CR1/Tau signalling has been widely discussed.
Keywords: Alzheimer's disease; CX3CR1 receptor; Fractalkine; microglia; Neuron; Tau

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

P301 L, an FTDP-17 mutant, exhibits enhanced glycation in vitro - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2020)
Background: Frontotemporal dementia and parkinsonism-linked to chromosome-17 are a group of diseases with tau mutations leading to primary tauopathies which include progressive supranuclear palsy, corticobas al syndrome, and frontotemporal lobar degeneration. Alzheimer's disease is a non-primary tauopathy, which displays tau neuropathology of excess tangle formation and accumulation. FTDP-17 mutations are responsible for early onset of AD, which can be attributed to compromised physiological functions due to the mutations. Tau is a microtubule-binding protein that secures the integrity of polymerized microtubules in neuronal cells. It malfunctions owing to various insults and stress conditions-like mutations and post-translational modifications. Objective: In this study, we modified the wild type and tau mutants by methyl glyoxal and thus studied whether glycation can enhance the aggregation of predisposed mutant tau. Methods: Tau glycation was studied by fluorescence assays, SDS-PAGE analysis, conformational evaluation, and transmission electron microscopy. Results: Our study suggests that FTDP-17 mutant P301 L leads to enhanced glycation-induced aggregation as well as advanced glycation end products formation. Glycation forms amorphous aggregates of tau and its mutants without altering its native conformation. Conclusion: The metabolic anomalies and genetic predisposition have found to accelerate tau-mediated neurodegeneration and prove detrimental for the early-onset of Alzheimer's disease.
Keywords: advanced glycation end products; Alzheimer's disease; FTDP-17; tau glycation

Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2020)
Background Alzheimer's disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-beta plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40(WT) oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-beta sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40(WT) oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11(+) Iba1(high) microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer's disease condition.
Keywords: Actin; activation; Alzheimer's disease; microglia; migration; neurodegeneration; Tau Oligomers; Tauopathy

Role of microglia in regulating cholesterol and tau pathology in alzheimer's disease - Nanjundaiah, Shwetha; Chidambaram, Hariharakrishnan; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Cholesterol, a principal constituent of the cell membrane, plays a crucial role in the brain by regulating the synaptic transmission, neuronal signaling, as well as neurodegenerative diseases. Defects in the cholesterol trafficking are associated with enhanced generation of hyperphosphorylated Tau and Amyloid-beta protein. Tau, a major microtubule-associated protein in the brain, is the key regulator of the mature neuron. Abnormally hyperphosphorylated Tau hampers the major functions related to microtubule assembly by promoting neurofibrillary tangles of paired helical filaments, twisted ribbons, and straight filaments. The observed pathological changes due to impaired cholesterol and Tau protein accumulation cause Alzheimer's disease. Thus, in order to regulate the pathogenesis of Alzheimer's disease, regulation of cholesterol metabolism, as well as Tau phosphorylation, is essential. The current review provides an overview of (1) cholesterol synthesis in the brain, neurons, astrocytes, and microglia; (2) the mechanism involved in modulating cholesterol concentration between the astrocytes and brain; (3) major mechanisms involved in the hyperphosphorylation of Tau and amyloid-beta protein; and (4) microglial involvement in its regulation. Thus, the answering key questions will provide an in-depth information on microglia involvement in managing the pathogenesis of cholesterol-modulated hyperphosphorylated Tau protein.
Keywords: Alzheimer's disease; Amyloid-beta protein; Cholesterol; microglia; Tau hyperphosphorylation

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Alpha-Linolenic acid inhibits Tau aggregation and modulates Tau conformation - Desale, Smita Eknath; Dubey, Tushar; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2021)
Alzheimer's disease is characterized by important patho-proteins, which being composed of Amyloid-beta, plaques and intracellular neurofibrillary tangles of Tau. Intrinsically disordered protein tau has several interacting partners, which are necessary for its normal functioning. Tau has been shown to interact with various proteins, nucleic acid, and lipids. alpha-Linolenic acid (ALA) a plant-based omega-3 fatty acid has been studied for its role as neuroprotective and beneficial fatty add in the brain. In this study, we are focusing on the ability of ALA to induce spontaneous assembly in tau protein. ALA inhibited the Tau aggregation as indicated by reduced ThS fluorescence kinetics, which indicates no aggregation of Tau. Similarly, SDS-PAGE analysis supported that ALA exposure inhibited the aggregation as no higher-order tau species were observed. Along with its ability to impede the aggregation of Tau, ALA also maintains a native random coiled structure, which was estimated by CD spectroscopy. Finally, TEM analysis showed that the formation of Tau fibrils was found to be discouraged by ALA. Hence, conclusion of the study suggested that ALA profoundly inhibited aggregation of Tau and maintained it's the random-coil structure. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-linolenic acid; Alzheimer's disease; Free fatty adds; Tau conformation; Tau fibrillization

Baicalein inhibits heparin-induced Tau aggregation by initializing non-toxic Tau oligomer formation - Sonawane, Shweta Kishor; Uversky, Vladimir N.; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Background: Amyloid aggregate deposition is the key feature of Alzheimer's disease. The proteinaceous aggregates found in the afflicted brain are the intra-neuronal neurofibrillary tangles formed by the microtubule-associated protein Tau and extracellular deposits, senile plaques, of amyloid beta (A beta) peptide proteolytically derived from the amyloid precursor protein. Accumulation of these aggregates has manifestations in the later stages of the disease, such as memory loss and cognitive inabilities originating from the neuronal dysfunction, neurodegeneration, and brain atrophy. Treatment of this disease at the late stages is difficult, and many clinical trials have failed. Hence, the goal is to find means capable of preventing the aggregation of these intrinsically disordered proteins by inhibiting the early stages of their pathological transformations. Polyphenols are known to be neuroprotective agents with the noticeable potential against many neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Prion diseases. Methods: We analyzed the capability of Baicalein to inhibit aggregation of human Tau protein by a multifactorial analysis that included several biophysical and biochemical techniques. Results: The potency of Baicalein, a polyphenol from the Scutellaria baicalensis Georgi, against in vitro Tau aggregation and PHF dissolution has been screened and validated. ThS fluorescence assay revealed the potent inhibitory activity of Baicalein, whereas ANS revealed its mechanism of Tau inhibition viz. by oligomer capture and dissociation. In addition, Baicalein dissolved the preformed mature fibrils of Tau thereby possessing a dual target action. Tau oligomers formed by Baicalein were non-toxic to neuronal cells, highlighting its role as a potent molecule to be screened against AD. Conclusion: In conclusion, Baicalein inhibits aggregation of hTau40 by enhancing the formation of SDS-stable oligomers and preventing fibril formation. Baicalein-induced oligomers do not affect the viability of the neuroblastoma cells. Therefore, Baicalein can be considered as a lead molecule against Tau pathology in AD.
Keywords: Alzheimer's disease; Baicalein; Tau dissolution; Tau inhibition; Tau Oligomers

Phosphoinositides signaling modulates microglial actin remodeling and phagocytosis in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Alzheimer's disease is one of the neurodegenerative diseases, characterized by the accumulation of abnormal protein deposits, which disrupts signal transduction in neurons and other glia cells. The pathological protein in neurodegenerative diseases, Tau and amyloid-P contribute to the disrupted microglial signaling pathways, actin cytoskeleton, and cellular receptor expression. The important secondary messenger lipids i.e., phosphatidylinositols are largely affected by protein deposits of amyloid-beta in Alzheimer's disease. Phosphatidylinositols are the product of different phosphatidylinositol kinases and the state of phosphorylation at D3, D4, and D5 positions of inositol ring. Phosphatidylinositol 3,4,5-triphosphate (PI 3, 4, 5-P3) involves in phagocytic cup formation, cell polarization, whereas Phosphatidylinositol 4,5-bisphosphate (PI 4, 5-P2)-mediates the process of phagosomes formation and further its fusion with early endosome.. The necessary activation of actin-binding proteins such as Rac, WAVE complex, and ARP2/3 complex for the actin polymerization in the process of phagocytosis, migration is regulated and maintained by PI 3, 4, 5-P3 and PI 4, 5-P2. The ratio and types of fatty acid intake can influence the intracellular secondary lipid messengers along with the cellular content of phaphatidylcholine and phosphatidylethanolamine. The Amyloid-beta deposits and extracellular Tau seeds disrupt phosphatidylinositides level and actin cytoskeletal network that hamper microglial-signaling pathways in AD. We hypothesize that being a lipid species intracellular levels of phosphatidylinositol would be regulated by dietary fatty acids. Further we are interested to understand phosphoinositide-based signaling cascades in phagocytosis and actin remodeling.
Keywords: actin remodeling; Alzheimer's disease; Dietary fatty acids; Phagocytosis; Phosphoinositides; PI3K signaling

Protriptyline improves spatial memory and reduces oxidative damage by regulating NF kappa B-BDNF/CREB signaling axis in streptozotocin-induced rat model of Alzheimer's disease - Tiwari, Virendra; Mishra, Akanksha; Singh, Sonu; Mishra, Sandeep Kumar; Sahu, Kiran Kumari; Parul; Kulkarni, Mahesh J.; Shukla, Rakesh; Shukla, Shubha (Brain Research, 2021)
Antidepressants are well known to exert their role via upregulation of brain derived neurotrophic factor (BDNF). BDNF has been reported to exerts its neuroprotective effect in rodent and primate models as well as in patients of Alzheimer's disease (AD). The aim of our study was to evaluate the effect of protriptyline (PRT), a tricyclic antidepressant, in streptozotocin (STZ)- induced rat model of AD. Total 10 mu l of STZ was injected into each ventricle (1 mg/kg). PRT (10 mg/kg, i.p.) treatment was started 3-day post STZ administration and continued till 21 days. We found that STZ treatment significantly increased pTau, A beta 42 and BACE-1 expression, oxidative stress and neurodegeneration in hippocampus and cortex of adult rats. STZ induced impairment in spatial learning and retention memory was associated with increased WO and reduced CREB and BDNF expression in cortex and hippocampus. Interestingly, PRT treatment significantly reduced pTau, A beta 42 and BACE-1 levels, neurodegeneration, oxidative stress and glial activation, contributing to the improved spatial learning and retention memory in STZ treated rats. Moreover, PRT treatment significantly improved p-ERK/ERK ratio and enhanced BDNF and CREB levels by reducing NFXB and GFAP expression in STZ treated rats. Our data suggest that impaired NFXB and CREB signaling potentially contribute in AD pathogenesis by elevating oxidative stress and neuroinflammation mediated neurodegeneration. Our study has established protriptyline as a multi target molecule in pre-clinical model of AD and further investigations on PRT like molecules could pave way for further development of effective new treatments in neurodegenerative disorders.
Keywords: Alzheimer's disease; antidepressant; BDNF; Memory; Oxidative stress; Protriptyline

G-protein coupled purinergic P2Y12 receptor interacts and internalizes Tau(RD)-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer's disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (Tau(RD)) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, Tau(RD) was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated Tau(RD) internalization has demonstrated activation of microglia with an increase in the Iba1 level, and Tau(RD) becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that Tau(RD) is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated Tau(RD) by lysosomal pathway. Altogether, microglial P2Y12R interacts with Tau(RD) and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer's disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau(RD)

TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization: a specialized Tau perspective - Kapoor, Mahima; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2023)
Microtubule-associated protein, Tau has been implicated in Alzheimer's disease for its detachment from microtubules and formation of insoluble intracellular aggregates within the neurons. Recent findings have suggested the expulsion of Tau seeds in the extracellular domain and their prion-like propagation between neurons. Transforming Growth Factor-beta 1 (TGF-beta 1) is a ubiquitously occurring cytokine reported to carry out immunomodulation and neuroprotection in the brain. TGF-beta-mediated regulation occurs at the level of neuronal survival and differentiation, glial activation (astrocyte and microglia), amyloid production-distribution-clearance and neurofibrillary tangle formation, all of which contributes to Alzheimer's pathophysiology. Its role in the reorganization of cytoskeletal architecture and remodelling of extracellular matrix to facilitate cellular migration has been well-documented. Microglia are the resident immune sentinels of the brain responsible for surveying the local microenvironment, migrating towards the beacon of pertinent damage and phagocytosing the cellular debris or patho-protein deposits at the site of insult. Channelizing microglia to target extracellular Tau could be a good strategy to combat the prion-like transmission and seeding problem in Alzheimer's disease. The current review focuses on reaffirming the role of TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization and considers utilizing the approach of TGF-beta-triggered microglia-mediated targeting of extracellular patho-protein, Tau, as a possible potential strategy to combat Alzheimer's disease.
Keywords: Alzheimer's disease; Cytoskeleton reorganization; Extracellular Tau; microglia; TGF-beta; TGF-beta 1